Mucoid impaction mimicking multiple metastatic lung cancer - Yi-Chih Huang; Hsu-Chao Chang; Yi-Hsin Lee; Mei-Chen Yang (Tzu Chi Medical Journal)
The most common etiology of multiple pulmonary nodules is metastatic lung cancer. Although benign etiologies have been reported, mucoid impaction less commonly presents as multiple pulmonary nodules. Herein, we report the case of an 81-year-old demented man who presented with multiple pulmonary nodules due to mucoid impaction. Chest radiographs revealed rapid resolution after tracheostomy and adequate mucus clearance. We suggest that mucoid impaction may present as multiple pulmonary nodules mimicking multiple metastatic lung cancer.